High-Flow Nasal Cannula Versus Bag-Valve-Mask for Preoxygenation Before Intubation in Subjects With Hypoxemic Respiratory Failure - Simon, Marcel; Wachs, Christian; Braune, Stephan; de Heer, Geraldine; Frings, Daniel; Kluge, Stefan (Respiratory care, 2016)
Critically ill patients with respiratory failure undergoing intubation have an increased risk of hypoxemia-related complications. Delivering oxygen via a high-flow nasal cannula (HFNC) has theoretical advantages and is increasingly used. This study was conducted to compare HFNC with bag-valve-mask (BVM) for preoxygenation and to assess oxygenation during intubation in subjects with hypoxemic respiratory failure. This study was a randomized controlled trial including 40 critically ill subjects with hypoxemic respiratory failure who received either HFNC or BVM for preoxygenation before intubation in the ICU. The primary outcome was the mean lowest SpO2 during intubation. The mean lowest SpO2 during intubation was 89 ± 18% in the HFNC group and 86 ± 11% in the BVM group (P = .56). In subjects receiving HFNC, a significant increase in SpO2 after preoxygenation was only seen in those previously receiving low-flow oxygen (P = .007), whereas there was no significant difference in SpO2 in subjects previously receiving noninvasive ventilation or HFNC (P = .73). During the 1 min of apnea after the induction of anesthesia, SpO2 dropped significantly in the BVM group (P = .001), whereas there was no significant decrease in the HFNC group (P = .17). There were no significant differences between the 2 groups at any of the predefined time points before or after intubation concerning SpO2 , PaO2 /FIO2 , and PaCO2 . Preoxygenation using HFNC before intubation was feasible and safe compared with BVM in critically ill subjects with acute, mild to moderate hypoxemic respiratory failure. There was no significant difference in the mean lowest SpO2 during intubation between the HFNC and the BVM group. There was also no significant difference in SpO2 between the 2 groups at any of the predefined time points. However, on continuous monitoring, there was a significant decrease in SpO2 during the apnea phase before intubation in the BVM group, which was not seen in the HFNC group. (ClinicalTrials.gov registration NCT01994928.).